Service quality, image and loyalty towards Malaysian hotels - Cham, Tat Huei; Easvaralingam, Yalini (InderScience, 2012)
The rapid growth of the hotel industry in the first decade of the 21st century forced hotel operators to critically acknowledge the importance of service improvement in order to gain competitive advantage. Therefore, identifying the factors that influence the quality of services of hotels is critical for the success of the hotels. Corporate image and customer loyalty should also be emphasised to ensure the sustainability of the hotels in this competitive industry. Hence, this study is conducted to discover the factors influencing perceived service quality of Malaysian hotels, as well as exploring the relationship between perceived service quality with customer loyalty and corporate image. Additionally, this study is one of the few studies on quality certification related to the demand perspective and also on the mediating role of image on the relationship between service quality and loyalty in the hotel industry.